Integritas dan Akuntabilitas dalam Pengelolaan Keuangan Sekolah atau Madrasah - Nor Mubin (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2018)
The issue of integrity and accountability has recently been increasingly discussed with the demands of the community for the importance of quality education, in accordance with the provisions in SBM. Integrity is acting consistently in accordance with organizational values ??and policies as well as professional code of ethics, even in circumstances that are difficult to do,